ChemInform Abstract: Well‐Defined Copper(I) Fluoroalkoxide Complexes for Trifluoroethoxylation of Aryl and Heteroaryl Bromides. Issue 38 (3rd September 2015) - Huang, Ronglu; Huang, Yangjie; Lin, Xiaoxi; Rong, Mingguang; Weng, Zhiqiang
Abstract Phenanthroline ligand‐supported copper(I) fluoroalkoxide complexes bearing a trifluoroethoxy, a pentafluoropropoxy or a tetrafluoropropoxy substituent are prepared and applied in the scalable synthesis of fluoroalkyl (hetero)aryl ethers.